Kissinger and Latin America : intervention, human rights, diplomacy - Rabe, Stephen G. (Book collections on Project MUSE., 2020)
"This book analyzes U.S. policies toward Latin America during a critical period of the Cold War when Henry Kissinger was serving as national security advisor and secretary of state"--